DEVELOPMENT AND ASSESSMENT OF SOCIAL SITES MEDIATED COURSE MODULE IN HIGHER EDUCATION - Kausar, Shabana; Khanam, Afifa ,; Quraishi, Uzma; Quraishi, Uzma (International Journal of Psychosocial Rehabilitation, 2020)
With the increasing hours spent on social media and growing dependability on collaborative technologies by youth, higher education institutes are exploiting social sites world over in their courses for wider communication. The present research harnesses the possibilities of introducing full courses on social sites to make educational opportunities more accessible, interesting, collaborative, flexible and interactive. The study involved a mix method research with both quantitative and qualitative paradigms and it was a research and development by purpose. An extensive analysis was conducted of existing social site courses for higher education and keeping in view the strengths and weaknesses of the existing programs, a contextualized social site module was designed by the researchers on ‘Instructional Technology Basics’. The module followed principle of 5Cs of online education; communication, collaboration, community, convergence and creativity. Two cohorts of 40 (total 80) mix ability, graduate and post graduate students were taught through Facebook with pre-test post-test experimental design within the population of higher education students of District Lahore, Pakistan. The pre and post tests were conducted through Survey Monkey incorporated in the course along with other formative assessments. After completion of each course session, electronic inbuilt interviews were conducted from the participants to find their experiences and reflections about how did they learn and their suggestions were sought for refining the course for increased effectiveness. The findings were encouraging enough to suggest all types of short and long theoretical courses to be taught through social sites, especially through Facebook. The study has implications for specific course designing and interactive tutoring at higher education using social sites.